Kansainvälinen vero-oikeus murroksessa: sääntelyalan modernisoitumisen askelmerkkejä - Urpilainen, Matti (Lakimies, 2025)
International tax law at a crossroads: Pathways to modernisation An OECD project on Base Erosion and Profit Shifting (BEPS) has brought significant changes to international tax law and to the international tax treaty system. Recent years have witnessed many changes to tax law rules in Finland and elsewhere, as required by the OECD recommendations, BEPS-related EU directives, and domestic policy considerations. The new regulatory measures have brought changes to countless technical details of tax legislation, but also to the underlying objectives and key operational principles of international tax law. The author discusses the broader normative and theoretical implications beneath the technical layer – how BEPS has changed and is about to change the nature of international tax law as a field of law. The ascent of multilateralism and changes in the sources of international tax law are highlighted in the analysis. The author concludes that recent developments have given rise to a need for the formation of new theory. In order to fully recognise and understand the normative impacts of recent changes in the field, practically-oriented legal analysis must be supplemented with conceptual and theoretical approaches.